Combined Stent Insertion and High-intensity Focused Ultrasound Ablation for Patients With Malignant Obstructive Jaundice. Issue 6 (December 2016) - Niu, Su; Cheng, Long; Qiao, Yan; Fu, Yu-Fei; Cao, Chi
Abstract : Purpose: We aimed to determine the clinical effectiveness of combined stent insertion and high-intensity focused ultrasound (HIFU) ablation for patients with malignant obstructive jaundice (MOJ). Materials and Methods: From June 2013 to May 2015, consecutive patients with inoperable MOJ underwent biliary stent with or without HIFU ablation in our center. Treatment-related complications, stent patency time, and survival time were compared between 2 groups. Results: During the enrolled time, a total of 51 patients with MOJ underwent biliary stent with HIFU ablation (n=24) or biliary stent only (n=27) in our center. There was no significant difference in baseline data between 2 groups. Relief of jaundice was achieved in all patients in both groups. Cholangitis was observed in 2 patients in stent with HIFU ablation group and 1 patient in stent only group ( P =0.483). Reobstruction of stent was observed in 4 patients in stent with HIFU ablation group and 8 patients in stent only group ( P =0.276). The mean stent patency time was 367±41 days in stent with HIFU ablation group and 257±35 days in stent only group ( P =0.037). The mean overall survival was 238±31 days in stent with HIFU ablation group and 152±20 days in stent only group ( P =0.014). Conclusions: Combined biliary stent insertion and HIFU ablation is a safe and easy method for patients with MOJ, and seems to extend stent patency time and survival when compared with biliary stent only.